2022
DOI: 10.1017/s1755773922000558
|View full text |Cite
|
Sign up to set email alerts
|

The makers get it all? The coalitional welfare politics of Populist Radical Right Parties in Europe. The case studies of Austria and Italy

Abstract: The article investigates whether and to what extent the welfare policies of Populist Radical Right Parties (PRRPs) vary in diverse government coalitions. Relying on a multidimensional framework differentiating coalitional politics along the welfare size and deservingness dimension, we conduct a comparative case study analysing welfare reforms of the ‘standard’ centre-right/PRRP government coalition ÖVP-FPÖ in Austria and the ‘new’ populist government coalition M5S-Lega in Italy. We find that both PRRPs do not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…A growing body of literature has suggested that PRRPs have developed a distinctive welfare state ideology, which combines defending a generous welfare state for 'deserving' members of the community with restrictive approache to 'undeserving' access to social benefits (Chueri, 2022;Enggist & Pinggera, 2021;Fischer & Giuliani;2023;Otjes, 2019). This literature has furthermore suggested that distinguishing 'deserving' and 'undeserving' is a function of nativist and authoritarian appeals (Ennser-Jedenastik, 2016, 2018Otjes et al, 2018;Rathgeb, 2021;Abts et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of literature has suggested that PRRPs have developed a distinctive welfare state ideology, which combines defending a generous welfare state for 'deserving' members of the community with restrictive approache to 'undeserving' access to social benefits (Chueri, 2022;Enggist & Pinggera, 2021;Fischer & Giuliani;2023;Otjes, 2019). This literature has furthermore suggested that distinguishing 'deserving' and 'undeserving' is a function of nativist and authoritarian appeals (Ennser-Jedenastik, 2016, 2018Otjes et al, 2018;Rathgeb, 2021;Abts et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Building on this conception, recent work on PRRPs' welfare positions has also challenged earlier claims of that the parties are 'blurring' their welfare preferences, advocating for a mix of right-and left-wing welfare policies (Rovny, 2013;Rovny & Polk, 2020). This ostensible incoherence results not from a 'blurred' welfare position but rather from a dualistic welfare platform: combining generous welfare state, based on income replacement, for the 'deserving', with upholding retrenchment, increase of conditionalities and workfare measures aimed at the 'undeserving' members of the community (Chueri, 2022;Enggist & Pinggera, 2021;Fischer & Giuliani;2023;Otjes, 2019).…”
Section: Introductionmentioning
confidence: 99%